Cultural and socio-economic determinants of natural dye usage: A case of African dye plants in Benin - Wouyou, Gbètoyénonmon Hyacinthe; Avocevou-Ayisso , Carolle; Idohou, Rodrigue; Assogbadjo, Cossi Sosthène; Boukari, Nouroudine Saley; Idi Abba, Mahaman Sabiou; Houndofi, Esquilin Balt; Assogbadjo, Achille Ephrem (Ethnobotany Research and Applications, 2025)
Background: The use of natural dyes in Benin varies across cultural and regional contexts. This study explores traditional knowledge and practices while testing Phillips and Gentry’s hypothesis linking plant utility to taxonomic group, growth form, abundance, and size. Methods: Ethnobotanical surveys were carried out in 31 communes (May–October 2024) with 722 participants selected using Dagnelie’s (1998) formula. Data on dye species, categories of use, determinants, and harvesting methods were analysed through informant consensus factor (ICF), fidelity level (FL), use value index (UVi), cultural importance index (CII), and statistical tests including Chi-square and correspondence factor analysis (CFA). Results: Food-related dye use had the highest ICF (0.98), followed by cosmetics (0.92). Daniellia oliveri (Rolfe) Hutch. & Dalziel recorded the highest UVi (1.00), while Corchorus olitorius L., Spondias mombin L., and Khaya senegalensis (Desv.) A.Juss. showed moderate values (0.33–0.50). Parkia biglobosa (Jacq.) R.Br. ex G.Don, Philenoptera cyanescens (Schumach. & Thonn.) Roberty, and Sorghum bicolor (L.) Moench were culturally significant. The dominant uses were food (31.89%) and medicine (24.60%). Influencing factors included ancestral knowledge (21.91%), colour (20.92%), rituals (15.51%), availability (8.57%), and accessibility (8.12%). CFA highlighted socio-cultural variation, while Chi-square revealed gender differences (p = 3.454e-05): women mainly used food dyes, men handicrafts. Occupation was also significant (p = 2.2e-16), with weavers, chiefs, and artisans as key users. Conclusions: Dye plant use in Benin is diverse and shaped by socio-cultural drivers. Results partly support Phillips and Gentry’s hypothesis. Further studies should evaluate species threats and promote sustainable conservation. Keywords: Producing-dye plants; indigenous dye plants, traditional knowledge; use determinant, Benin